Effectiveness techniques of resources and expenditures marketing - Taghieh, Sediegheh; Khatami, Seyed Keivan (Ciência e Natura, 2015)
Marketing is one of the strategies which can increase bank revenues. Principles and techniques of marketing in view of their applied approaches with regard to bank′s financial resources and expenditures and the kind of relationship with clients and practical solutions in order to change and improve clich′e behaviors can be as one of the effective tools in the improvement of behavioral patterns of today′s competitive environment. Progress of relationship marketing in bank can be done in line of developing relationship with clients. keeping relationship with clients is a long-term phenomenon and instead of on-going results future impacts should be the center of attention. In this study concurrent with surveying relationship marketing some cases of their techniques can be studied in general. The method of study, is library method. the result indicates that important factors in the success of banks is to provide rapid services and satisfaction of clients. Therefore dynamic and innovative organization should comply with environment and increasing demands of clients.Then with careful and effective marketing we can realize our purpose of gaining benefit.